The Influence of Marketing Strategies on Sales Turnover of Bengkulu City's Specialty Food Products - Tiara, Tiara; Bahrin, Bahrin; Duharman, Duharman (Jurnal Pendidikan Rafflesia, 2025)
Marketing strategy plays an important role in marketing a product. The problems raised in this study are: (1) what is the marketing strategy carried out by traders of typical Bengkulu city pendap food (2) what is the sales turnover of typical Bengkulu city pendap food (3) is there an influence of marketing strategy on the sales turnover of typical Bengkulu city pendap food. This study aims (1) to determine the marketing strategy carried out by traders of typical Bengkulu city pendap food (2) to determine the sales turnover of typical Bengkulu city pendap food (3) is there an influence of marketing strategy on the sales turnover of typical Bengkulu city pendap food. This study aims (1) to determine the marketing strategy carried out by traders of typical Bengkulu city pendap food (2) to determine the sales turnover of typical Bengkulu city pendap food (3) to determine the influence of marketing strategy on the sales turnover of typical Bengkulu city pendap food This study uses quantitative research with a quantitative approach. The population of this study was 20 Bengkulu city's typical pendap traders. Data collection used observation, questionnaires and documentation. The data analysis technique used simple linear regression. From the results of my research, marketing strategies do not have a significant effect on the sales turnover of Bengkulu City's typical food products, this is in contrast to the research conducted by Chairani Putri (2020), with the research title "The Influence of Marketing Strategies on Sales Turnover of Tat Cake Products at the Bengkulu City Typical Souvenir Shopping Center". The results of the study showed that marketing strategies had a positive and significant effect on the sales turnover of Bengkulu City's typical tat cakes. This shows that this marketing strategy is an important thing to plan for business people or entrepreneurs because marketing strategies determine sales turnover and likewise sales turnover greatly determines profit or profit. This also determines how the business or business will develop in the future.